Maëlle Dupon : voyage au cœur des sens - Marine Mazars (Revue des Langues Romanes)
Maëlle Dupon is a multi-faceted author: poet, short story writer and translator. A Montrealer by adoption, she continues to express herself mainly in occitan and french. From a youth spent travelling, discovering others — and in the process discovering herself — and from life's experiences — sometimes happy, sometimes heartbreaking or sensual — she nourishes a colourful, vibrant and committed work. La color lenta de la pluèja, the author's first collection, offers an initiatory journey into the depths of the self. The texts written a posteriori give a glimpse of a new aesthetic experimentation that invites the reader to appropriate the raw text in order to reflect its full depth.